1990
DOI: 10.1002/ctpp.2150300514
|View full text |Cite
|
Sign up to set email alerts
|

Emissionspectroscopic Investigation of Bci3 Discharges

Abstract: Radiofrequency discharges in neat BCI, exhibit 3 broad molecular emissions with intensity maxima at about 305,350, and 480 nm. The 350 nm system consists of a progression of bands with an average separation of about 130 cm-l. All three emissions have an identical excitation kinetics in pulse discharges and are, therefore, believed to originate from the same emitter. Arguments are given that the emitter might be electronically excited BCI,.The dominant process of BCI(A) formation in neat BCI, at low r.f. power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Its main advantages in comparison to later methods [52,53,55,56] are: (i) the possibility of taking into account various secondary excitation (stepwise excitation, dissociative recombination, etc) and deactivation processes (collisional quenching, stepwise ionization, etc) [51,57]; and (ii) its ability to work with arbitrary shapes of the EEDF, which is known to be far from Maxwellian in hydrogen-containing discharge plasmas (see, e.g. [7]). The necessity for absolute spectroscopic and Langmuir probe measurements is its main disadvantage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its main advantages in comparison to later methods [52,53,55,56] are: (i) the possibility of taking into account various secondary excitation (stepwise excitation, dissociative recombination, etc) and deactivation processes (collisional quenching, stepwise ionization, etc) [51,57]; and (ii) its ability to work with arbitrary shapes of the EEDF, which is known to be far from Maxwellian in hydrogen-containing discharge plasmas (see, e.g. [7]). The necessity for absolute spectroscopic and Langmuir probe measurements is its main disadvantage.…”
Section: Methodsmentioning
confidence: 99%
“…Only a limited number of studies using the spectroscopic approach for boron containing plasmas can be found in the literature. Breitbarth and Ducke used optical emission spectroscopy (OES) to study excitation channels using intensity-time functions of selected emissions in the active phase and the afterglow of the pulsed RF discharge in BCl 3 and BCl 3 -Ar [7]. Schaffnit et al [14] utilized a RF discharge in BCl 3 -N 2 -H 2 -Ar mixtures for BN coating by PECVD.…”
Section: Introductionmentioning
confidence: 99%
“…The spectroscopic determination of the degree of dissociation of hydrogen in non-equilibrium plasmas was first reported in [9][10][11] and further developed in [12][13][14][15][16]. Recently it was shown that an account of the fine structure in balance equations is very important for the calculation of emission rate coefficients of direct and dissociative excitation of H α and H β lines [17].…”
Section: Methodsmentioning
confidence: 99%
“…This process was found to be very efficient in low-pressure (10-40 Pa) r.f. discharges where BCl 3 degree of decomposition is low [13].…”
Section: Production Of Radiative Species In Ar-bcl 3 Dischargementioning
confidence: 99%
“…A discussion on B 2 band emission is reported in [5] with new observed transitions from this molecule. Atomic boron lines (λ = 208.9 and 249.7 nm) which are currently used to characterize BCl 3 plasma [11][12][13][14] cannot be detected with our OES arrangement. As concerns the three unidentified transitions (λ = 563.5 nm, 581.9 nm and 582.2 nm) reported in our previous study of this Ar-BCl 3 microwave plasma [5], the line at λ = 563.5 nm is now assigned to the 4p 2 P 0 → 3s 2 S transition of atomic boron.…”
Section: The Ar-bcl 3 Plasma Emissionmentioning
confidence: 99%